EXPERT EVALUATION OF PEDAGOGICAL CONDITIONS FOR THE DEVELOPMENT OF ENTREPRENEURIAL COMPETENCE FUTURE PERFORMING ARTISTS (Innovative professional education, 2024)
To revive the domestic creative industry, it is crucial to saturate the national labor market with self-reliant, creative, and responsible professionals capable of working and creating jobs in conditions of instability to ensure sustainable development of Ukrainian society in the future. This can be achieved by creating educational conditions in institutions that are necessary for developing future performing artists' readiness forentrepreneurial activity, ability for various forms and methods of self-expression, creative critical thinking,initiative, perseverance, and social responsibility. Twelve priority pedagogical conditions for the development ofentrepreneurial competence future performing artists have been selected and expert evaluation of theirimportance has been conducted. The pedagogical conditions have been ranked, identifying the four mostsignificant ones. The coefficient of concordance has been calculated to assess the consensus of expert opinions, indicating moderate agreement of opinions. The Pearson's agreement criterion has confirmed the reliability of the obtained results.
Keywords: entrepreneurial competence, expert evaluation, pedagogical conditions, youth entrepreneurship, performing artists